Performance investigation of nanofluids as working fluid in a thermosyphon air preheater - Leong, K.Y.; Saidur, Rahman; Mahlia, T.M.I.; Yau, Y.H. (International Communications in Heat and Mass Transfer, 2012)
In recent years, there has been a substantial increase in energy demand due to industrialization development. This raises concern on issues such as depletion of fossil based energy and emission of green house gasses. Hence, optimization of energy use through the thermosyphon air preheater is one of the possible approaches to address this problem. It can be used to recover and transmit the heat from the hot air (flue gas) to the cold air used for combustion process in a boiler. This study focuses on the analytical analysis of the thermal performance of a thermosyphon operated with water and nanofluids. The thermo physical properties of the selected nanofluids and relevant formulations are taken from the literatures to perform the analysis. Study found that change of nanofluid properties such as thermal conductivity only plays minor role in enhancing the thermal performance of the thermosyphon. The study implied that the hot air velocity is capable of increasing the efficiency of a thermosyphon. It is found that 23 overall heat transfer enhancement is observed when the hot air velocity increases from 2.0. m/s to 4.75. m/s for water based (7) alumina and (4) titanium dioxide nanofluids.